2001
DOI: 10.1002/jnr.10085
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of glutathione in hippocampal neurons and glia in culture using monochlorobimane

Abstract: Glutathione (GSH) is a major antioxidant system in the mammalian central nervous system (CNS). Abnormalities of GSH metabolism have been associated with many disorders of the CNS, including Parkinson's, Alzheimer's, and Huntingdon's diseases and ischaemic/reperfusion injury. Investigation of GSH levels in the CNS generally relies on biochemical assays from cultures enriched for different cell types. Because glia influence neuronal metabolism, we have studied cultures in which neurons and glia are cocultured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 49 publications
7
80
1
Order By: Relevance
“…Surprisingly, we found that increasing pyruvate in the medium was detrimental for development, as a significantly lower percentage of blastocysts was consistently obtained (23.8±3.5%, n=87 embryos, four replicates) compared with control conditions (66.5±1.4%, n=95 embryos, four replicates, P<0.015). Furthermore, the inhibition of development by 1 mmol/l pyruvate could be rescued by adding the membrane-permeant antioxidant TEMPO [48.9±2.6% of blastocysts, n=94 embryos, four replicates versus 23.8±3.5% with high pyruvate only, P<0.005 (Keelan et al, 2001)]. This observation demonstrates that such a concentration of pyruvate is not toxic by itself, as has been reported earlier (Wales and Whittingham, 1971), and indicates that an oxidant action of pyruvate inhibits development.…”
Section: Impact Of Redox Potential In Early Developmentsupporting
confidence: 70%
See 1 more Smart Citation
“…Surprisingly, we found that increasing pyruvate in the medium was detrimental for development, as a significantly lower percentage of blastocysts was consistently obtained (23.8±3.5%, n=87 embryos, four replicates) compared with control conditions (66.5±1.4%, n=95 embryos, four replicates, P<0.015). Furthermore, the inhibition of development by 1 mmol/l pyruvate could be rescued by adding the membrane-permeant antioxidant TEMPO [48.9±2.6% of blastocysts, n=94 embryos, four replicates versus 23.8±3.5% with high pyruvate only, P<0.005 (Keelan et al, 2001)]. This observation demonstrates that such a concentration of pyruvate is not toxic by itself, as has been reported earlier (Wales and Whittingham, 1971), and indicates that an oxidant action of pyruvate inhibits development.…”
Section: Impact Of Redox Potential In Early Developmentsupporting
confidence: 70%
“…After the autofluorescence imaging, the increase in MCB fluorescence (exc: 360 nm; em: 470 nm longpass) of oocytes incubated in 12.5 mol/l MCB was continuously imaged for 40 to 90 minutes until a plateau was observed (for details, see Keelan et al, 2001). In order to compare experiments done on different days, the level of GSH fluorescence is expressed as a percentage of the fluorescence emitted from a control embryo (untreated M2 oocyte or GV oocyte) imaged simultaneously.…”
Section: Measurement Of Intracellular Gshmentioning
confidence: 99%
“…Monochlorobimane (MCB) forms a fluorescence adduct with GSH in a reaction catalyzed by glutathione-s-transferase (GST), allowing measurement of GSH cellular content. 24 A BASIC RESEARCH www.jasn.org steady-state fluorescence signal was reached by 50 min, and the signal was significantly greater in the PT (mean fluorescence intensity increase per tubule after 60 min 48.8 Ϯ 2.5%; n ϭ 40 tubules from four separate slices) than in the DT (mean increase per tubule 17.0 Ϯ 3.6%; n ϭ 26 tubules from four separate slices; P Ͻ 0.001; Figure 6, D and E). These findings are consistent with a higher level of GSH in the PT than in the DT.…”
Section: Ros Productionmentioning
confidence: 99%
“…We used monochlorobimane as a semi-quantitative measure of GSH status in the mixed cultures. This is a nonfluorescent compound which is conjugated to GSH through a reaction catalysed by glutathione-S-transferase and so gives a 'snapshot' of GSH content (Keelan et al 2001). In mixed cultures, confocal imaging with a UV laser allows measurements of the GSH levels in both neurons and astrocytes side by side in the same culture, a differentiation aided by the tendency of neurons to grow in a focal plane above that of the astrocyte layer.…”
Section: Ab and Oxidative Stressmentioning
confidence: 99%